Research on the resource and governance effects of state-owned equity participation: Based on the analysis of the green transformation process and path of private enterprises - Haizhi Ren; Yani Wen (PLoS ONE, 2025)
Against the backdrop of environmental challenges and resource constraints, deepening mixed ownership reform and promoting green development of enterprises have become a significant trend, and the resource and governance effects arising from the state-owned (SOE) equity participation in private enterprises (PEs) have become a prominent research topic. The article empirically examines the influence of state-owned equity involvement on the green transformation of private firms using a two-way fixed effects model, utilizing a sample of Shanghai and Shenzhen A-share listed private enterprises from 2013 to 2022. The results indicate that SOE equity participation considerably speeds up the green transformation process of PEs, and the conclusion remains consistent following several robustness tests. Through the two channels of financing efficiency and environmental information disclosure, SOE equity participation encourages the green transformation of PEs; management compensation incentives have a positive moderating effect on SOE equity participation and the green transformation of PEs. According to heterogeneity analyses, SOE ownership has a stronger motivating effect on PEs’ green transformation for large-scale, high-tech, and eastern area firms. The findings enrich the inquiry into the economic effects of reverse mixed reform and establish practical methods and theoretical foundations for private enterprises to promote green transformation.